Socio Economic Impact of NITAQAT in Kerala - Ismayil P
One of the burning issues discussing at present related with the gulf expatriates is the implementation of saudization ‘Nitaqat’ in Saudi Arabia. This is an attempt to bring the facts on the newest Saudization policy of Saudi Arabia Kingdom ‘Nitaqat’, its implications and impacts on Kerala. There are about 5.74 lakh Keralites in the gulf countries. Saudization policy is expected to affect Kerala workers who employed in red zone, illegal residents and unauthorized entrepreneurs. Here the purpose of this work is to find out the impact of Nitaqat in kerala and its multiplier effect on various sectors including employment sectors of Kerala. The paper also attempts to make suggestion to manage the situation emerged following the ‘Nitaqat’.